2017
DOI: 10.4155/fmc-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Modulating 5-Ht 4 and 5-Ht 6 Receptors in Alzheimer’S Disease Treatment

Abstract: Alzheimer's disease (AD) is the most common form of dementia affecting millions of patients worldwide which can only be treated with symptomatic drugs. Among the numbers of biological targets which are today explored in order to prevent or limit the progression of AD, the modulation of 5-HTR and 5-HTR appeared to be promising. This modulation has been proved to enhance the cognition in AD through modulation of the neurotransmitter system but could also be beneficial in order to limit the amyloid pathology. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…5-HT 6 receptor antagonists have been extensively studied and there is a large consensus that they have pro-cognitive properties. Numerous studies have shown unequivocal beneficial effects of 5-HT 6 receptor antagonists on cognitive deficits in rodent models of psychiatric and neurodegenerative diseases such as schizophrenia and AD and have been extensively reviewed elsewhere (de Bruin and Kruse, 2015;de Jong and Mork, 2017;Ferrero et al, 2017;Khoury et al, 2018;Lalut et al, 2017). Though 5-HT 6 receptor blockade raised an important hope as symptomatic treatment to improve cognition in AD, the initial enthusiasm was tempered by the recent failure of leading compounds in Phase 3 trials.…”
Section: Antagonistsmentioning
confidence: 99%
“…5-HT 6 receptor antagonists have been extensively studied and there is a large consensus that they have pro-cognitive properties. Numerous studies have shown unequivocal beneficial effects of 5-HT 6 receptor antagonists on cognitive deficits in rodent models of psychiatric and neurodegenerative diseases such as schizophrenia and AD and have been extensively reviewed elsewhere (de Bruin and Kruse, 2015;de Jong and Mork, 2017;Ferrero et al, 2017;Khoury et al, 2018;Lalut et al, 2017). Though 5-HT 6 receptor blockade raised an important hope as symptomatic treatment to improve cognition in AD, the initial enthusiasm was tempered by the recent failure of leading compounds in Phase 3 trials.…”
Section: Antagonistsmentioning
confidence: 99%
“…14 In addition to those classical targets, the serotonergic system appears of particular interest, notably via the modulation of 5-HT 4 and 5-HT 6 receptors. 17,18 The activation of 5-HT 4 receptors (5-HT 4 R) with partial agonists, such as RS67333, is of particular interest as it can promote the non-amyloidogenic cleavage of Amyloid Protein Precursor (APP) and subsequently decrease the amyloid load in AD transgenic mice models. 19,20 In this context, we have in the past modulated the structure of RS67333 in order to introduce another target of choice for the treatment of AD such as acetylcholinesterase (AChE) inhibitory activity 21,22 or 5-HT 6 R antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the context of AD, the activation of 5-HT 4 Rs with agonist has led to the increase in neurotransmitter release as well as a clear impact of amyloid load in transgenic mice models after chronic administration. Several 5-HT 4 R agonists have been studied in clinical trials in recent years to demonstrate both symptomatic and disease-modifying effect against AD [ 11 ]. Beside this receptor subtypes, other serotonin receptors have been studied in the field of neurodegenerative diseases [ 12 ], such as the 5-HT 6 R [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%